Bramblestar's Storm: Warriors Super Edition #7 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2014)
"As the new leader of ThunderClan, Bramblestar must prepare to weather a storm the likes of which the warrior Clans have never seen--and might not survive"--.
"Warriors Super Edition."
"Exclusive manga adventure inside!"--Jacket cover.
New Kids Book Winter 2023.
Keywords: Fantasy; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Animals / Cats; JUVENILE FICTION / Action & Adventure / General; Cats -- Fiction